RECONSTRUCTING THE HARMONIZATION OF SCIENCE AND RELIGION THROUGH PROBLEM-BASED LEARNING TO DEVELOP HIGHER-ORDER THINKING SKILLS (HOTS) IN ELEMENTARY SCHOOL STUDENTS: AN SLR - Risna Afiana; Finka Putri Shoumi; Nia Ansyafani; Nanang Hasan Susanto (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2026)
The development of 21st-century education demands that students possess Higher Order Thinking Skills (HOTS) supported by meaningful, character-oriented learning. However, the implementation of learning in elementary schools still shows a dichotomy between science and religion, so that the learning process has not been able to optimally develop higher-order thinking skills and spiritual values. This study aims to reconstruct the harmonization of science and religion through the application of Problem Based Learning (PBL) in the development of HOTS in elementary school students. The study used a qualitative approach with the Systematic Literature Review (SLR) method. Data were obtained from scientific articles published in the period 2019–2025 through the Google Scholar, Garuda, ERIC, and Scopus databases. The review process was carried out through identification, selection, data extraction, synthesis of findings, and content analysis of 30 articles that met the inclusion criteria. The results of the study indicate that PBL is effective in improving higher-order thinking skills, especially in the aspects of analysis, evaluation, and creation, while also improving students' critical thinking, problem-solving, communication, and collaboration skills. The integration of religious values ​​in each stage of PBL provides a more holistic learning experience by connecting scientific phenomena and spiritual values. However, its implementation still faces obstacles such as limited teacher competency, limited learning time, and a lack of integrated learning tools. This research confirms that harmonizing science and religion through PBL is a relevant strategy for developing students' intellectual and spiritual intelligence. Therefore, the development of learning tools and teacher training are necessary for optimal implementation of this model in elementary schools.